Enzyme 15‐lipoxygenase 1 promotes hypoxia‐inducible factor 1α turnover and reduces vascular endothelial growth factor expression: implications for angiogenesis. (25th March 2014) - Zhong, Hua; Wang, Ruoxiang; Kelavkar, Uddhav; Wang, Christopher Y.; Simons, Jonathan
Abstract Hypoxia‐inducible factor 1α (HIF‐1α) is the regulatory subunit of the heterodimeric HIF‐1 that plays a critical role in transcriptional regulation of genes in angiogenesis and hypoxic adaptation, while fatty acid metabolism mediated by lipoxygenases has been implicated in a variety of pathogeneses, including cancers. In this study, we report that 15‐lipoxygenase 1 (15‐LO1), a key member of the lipoxygenase family, promotes HIF‐1α ubiquitination and degradation. Altering the level of 15‐LO1 yields inverse changes in HIF‐1α and HIF‐1 transcriptional activity, under both normoxia and hypoxia, and even in CoCl2‐treated cells where HIF‐1α has been artificially elevated. The antagonistic effect of 15‐LO1 is mediated by the Pro564/hydroxylation/26S proteasome system, while both the enzymatic activity and the intracellular membrane‐binding function of 15‐LO1 appear to contribute to HIF‐1α suppression. Our findings provide a novel mechanism for HIF‐1α regulation, in which oxygen‐dependent HIF‐1 activity is modulated by an oxygen‐insensitive lipid metabolic enzyme.